2018
DOI: 10.1002/adma.201705197
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of the Reversible O2−/O Redox Process in Li‐Rich Cathode Materials

Abstract: Conventional cathodes of Li-ion batteries mainly operate through an insertion-extraction process involving transition metal redox. These cathodes will not be able to meet the increasing requirements until lithium-rich layered oxides emerge with beyond-capacity performance. Nevertheless, in-depth understanding of the evolution of crystal and excess capacity delivered by Li-rich layered oxides is insufficient. Herein, various in situ technologies such as X-ray diffraction and Raman spectroscopy are employed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
249
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 312 publications
(268 citation statements)
references
References 50 publications
15
249
1
3
Order By: Relevance
“…Meanwhile, upon charging to 4.7 V, the position of the (003) peak shifted to a higher 2θ value, while the (101) and (113) reflections remained at the previous 2θ values, indicating that some different reactions occur in this voltage range. This opposite shift in the (003) reflection patterns may be caused by the extraction of Li + from the transition metal layer and not from the Li layer, resulting in the decrease in the capacity retention. During discharging, the (101) and (113) reflections shifted toward lower 2θ values due to the expansion of a ‐axis.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, upon charging to 4.7 V, the position of the (003) peak shifted to a higher 2θ value, while the (101) and (113) reflections remained at the previous 2θ values, indicating that some different reactions occur in this voltage range. This opposite shift in the (003) reflection patterns may be caused by the extraction of Li + from the transition metal layer and not from the Li layer, resulting in the decrease in the capacity retention. During discharging, the (101) and (113) reflections shifted toward lower 2θ values due to the expansion of a ‐axis.…”
Section: Resultsmentioning
confidence: 99%
“…This result leads to superior stability of Li 0.2 Na 1.0 Mn 0.8 O 2 ‐based sodium ion batteries compared with Na 1.2 Mn 0.8 O 2 . Although the crystal structure fails to return back to pristine state, it hardly changes during changed as well as in discharge process . DFT calculation was also exerted to quantitatively analyze the volume change during cycles.…”
Section: Resultsmentioning
confidence: 99%
“…One researcher proposed oxygen oxidation proceeds via O 2− to O − to O 2 − to O 2 , as inferred by the progressively contracted OO bonds from 2.75 to 1.21 Å, which appears rational as the oxygen evolution must go through gradual steps. In recent studies, the reversible O 2− /O − redox process during the initial two cycles has been demonstrated using in situ Raman spectra (Figure e) . In addition, one researcher has demonstrated that oxygen oxidation in LLOs mainly occurs by extracting labile electrons from unhybridized O 2p states sitting in LiOLi configurations unrelated to any hybridized TMO states (Figure c) …”
Section: Electrochemical Reaction Mechanisms Of Layered–layered Compomentioning
confidence: 93%
“…The related voltage profiles are shown for clarity. Reproduced with permission . Copyright 2018, WILEY‐VCH.…”
Section: Electrochemical Reaction Mechanisms Of Layered–layered Compomentioning
confidence: 99%